Improvement of some techno-functional properties of aquafaba by pre-fermentation with Lactobacillus plantarum MA2 - Bekiroglu, Hatice; Karimidastjerd, Atefeh; Ozmen, Duygu; Toker, Omer Said; Inan, Mehmet; Sagdic, Osman; Dertli, Enes (ELSEVIER, 2023)
Recently, modification of macromolecules in food products has gained special interest to increase their utilization during food processing. In this respect, the aim of this study was to modify chickpea aquafaba by using a pre-fermentation process with Lactobacillus plantarum MA2 for 3, 6 and 9 h and physicochemical and technofunctional of the modified aquafaba samples were investigated. The results showed that fermentation significantly improved foaming expansion, solubility and stability, with shorter fermentation times resulting in lower stability. Emulsifying properties were also improved by fermentation, with the 3-h fermentation sample having significantly higher emulsion stability. The protein profiles of chickpea during fermentation were analyzed using SDS-PAGE, and changes in the secondary structure of proteins were examined using FTIR spectroscopy. The major bands of low-molecular weight proteins were observed between 6.5 and 66 kDa, with minor bands between 66 and 200 kDa distributed similarly across all samples. The longer period of fermentation resulted in the formation of higher amounts of lower peptides. FTIR spectroscopy revealed changes in the secondary structure of proteins during fermentation, particularly in the amide-I region, which is sensitive to changes in the secondary structures of proteins consisting of layers such as the & alpha;-helix, & beta;-turn, & beta;-sheet, and random coil. Rheological properties of the aquafaba solution were investigated and all solutions showed shear thinning behavior while Ostwald de Waele model well described the flow behavior. The findings of the study highlighted that fermentation can be used as safe, eco-friendly, and green method for improving techno-functional characteristics of chickpea aquafaba.
Keywords: Aquafaba; Modification; Pre-fermentation; ISOELECTRIC PRECIPITATION; EMULSIFYING PROPERTIES; PROTEOLYTIC ACTIVITY; BY-PRODUCTS; PROTEINS; CHICKPEA; WATER; FERMENTATION; FORMULATION; FRACTIONS; Food Science & Technology